Meminimalisir Keterlambatan Waktu dan Pembengkakan Biaya Proyek Pembangunan Gedung Kecamatan Dongko, Trenggalek dengan Metode Nilai Hasil (Earned Value Method) - Mohammad Bismo Febriantoro; Sony Susanto; Eko Siswanto (Kadiri University, 2022)
The construction of the Dongko Trenggalek District Building is one of the Trenggalek government's work programs in an effort to improve the quality of community services. In the construction of a building, proper project management needs to be done to minimize the occurrence of project failures. This study aims to minimize delays and cost overruns in the Dongko District Building Project, Trenggalek. Efforts to control the project are carried out with the result value method. EVM is one of the methods used to measure and evaluate the progress and performance of a project The result value method is applied by performing performance analysis which includes cost and schedule analysis, variance analysis, performance index analysis and cost estimation analysis and work end time. The project was built with a contract value of Rp. 2,902,468,0000.00 and is planned to be completed within 154 days. The results showed that the project experienced delays from what was planned. The completion time was delayed from the planned time from 154 days to 170 days with a total project cost of Rp. 2,932,467,150 which indicates that the budgeted costs for the work carried out experienced overhead or cost overruns. By knowing this, the implementer can evaluate the work early so as to minimize the occurrence of project failure.